O oblubieńczym i rodzicielskim sensie ludzkiego ciała - Kupczak, Jarosław (Verbum Vitae, 2022)
The anthropological dualism characteristic of contemporary culture divides the human being into two distinct spheres: material and spiritual. As a result, it is almost impossible to talk meaningfully today about certain topics of fundamental importance: the body, sex, and sexuality. In his philosophical and theological anthropology, John Paul II challenged this error by creating the concept of the spousal and parental sense of the body. The present article is an attempt to apply this concept, key to the so-called “Theology of the Body” of John Paul II. Through critical reflection we can arrive at a broader understanding of fatherhood and motherhood, a way of thinking that breaks the bond between the biological origin of a child and the emotional, real bond formed with his or her parents.